(untitled) (Fiep Bulletin - online, 2014)
From bibliographic analysis of authors from vanguard and grounded in psychoanalytic perspective, one can notice the effect of the production of schooling in subjects that require a careful and often a sense production as significant marks of this process, the difficulties that students with learning disabilities have on their overall development, it is considered necessary to offer them a learning environment that helps them to abandon the passive attitude of receivers of knowledge. An environment where they are valued and encouraged their creativity and initiatives , allowing them greater interaction with people and the environment they live in , not leaving their limitations and difficulties, but the emphasis on the development potential of each confined and betting in your abilities, aspirations, growth and integration into the community. In an inclusive school children with global developmental disorders "TGD’s", should receive the extra support needed to ensure them a real education. Soon the school implications consist in the payment of equal value and rights, and the consequent taking action at all levels (political, governmental, social, community, individual), reflecting consistency between what is said and what is speech.